Reader-interest classifications: An alternative arrangement for libraries - Martínez-Ávila, Daniel [UNESP] (My University, 2017)
The concept of reader-interest classifications and its related terminology have shown a well-established presence and common characteristics in the knowledge organization literature for more than half a century. During the period 1952-1995, it was not unusual to find works, projects and discourses using a common core of characteristics and terms to refer to a recognizable type of projects involving alternative classifica- tions to the DDC and other traditional practices in libraries. The use of reader-interest classification related terms and references drastically declined since 1995, although similar projects and characteristics are being used until the present day such as those of implementation of BISAC in American public libraries. The present paper attempts to overview the concept and terminology of reader-interest classifications in a historical perspective emphasizing the transformation of the concept and its remaining characteristics in time.
Keywords: Categories; Libraries; Reader interest classifications; Users